Fault Friction During Simulated Seismic Slip Pulses. Issue 8 (15th August 2021) - Harbord, Christopher; Brantut, Nicolas; Spagnuolo, Elena; Di Toro, Giulio
Abstract: Theoretical studies predict that during earthquake rupture faults slide at non‐constant slip velocity, however it is not clear which source time functions are compatible with the high velocity rheology of earthquake faults. Here we present results from high velocity friction experiments with non‐constant velocity history, employing a well‐known seismic source solution compatible with earthquake source kinematics. The evolution of friction in experiments shows a strong dependence on the applied slip history, and parameters relevant to the energetics of faulting scale with the impulsiveness of the applied slip function. When comparing constitutive models of strength against our experimental results we demonstrate that the evolution of fault strength is directly controlled by the temperature evolution on and off the fault. Flash heating predicts weakening behavior at short timescales, but at larger timescales strength is better predicted by a viscous creep rheology. We use a steady‐state slip pulse to test the compatibility of our strength measurements at imposed slip rate history with the stress predicted from elastodynamic equilibrium. Whilst some compatibility is observed, the strength evolution indicates that slip acceleration and deceleration might be more rapid than that imposed in our experiments. Plain Language Summary: Faults, where deformation is hosted in the upper portion of the crust, slide rapidly during earthquakes. Unfortunately how faults slip during earthquakes is not clear, with several theoretical models proposed whereby newtons second law is satisfied. Consequently we test the strength of rocks during one proposed slip history. Key observations show that strength evolution strongly depends on slip history. Temperature is also shown to be a key factor governing strength evolution, and weakening at short timescales is controlled by heating at highly stressed contacts before viscous processes accommodate deformation. Histories of realistic fault slip and compatible strength changes do not completely agree with experimental measurements. Instead we suggest that faults must accelerate and decelerate more rapidly than current models. Significantly, rapid acceleration and deceleration of faults will promote more damaging high frequency wave radiation. Key Points: We investigate the evolution of fault strength during realistic earthquake slip history High velocity carbonate built fault strength is compatible with flash heating at short timescales and viscous creep at larger timescales We observe limited elastodynamic compatibility between measured fault strength and imposed slip history